2018
DOI: 10.1002/jnr.24264
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural changes associated with aberrant functional responses to the Valsalva maneuver in heart failure

Abstract: Heart failure (HF) patients show inability to regulate autonomic functions in response to autonomic challenges. The autonomic deficits may stem from brain tissue injury in central autonomic regulatory areas, resulting from ischemic and hypoxic processes accompanying the condition. However, the direct evaluation of correlations between brain structural injury and functional timing and magnitude of neural signal patterns within affected areas, which may lead to impaired autonomic outflow, is unclear. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
(99 reference statements)
1
14
0
Order By: Relevance
“…In addition, our work reinforces some studies showing functional and structural alterations of the insula in cardiovascular diseases such as hypertension (Marins, Iddings, Fontes, & Filosa, ) or heart failure (Song, Roy, Fonarow, Woo, & Kumar, ). These insula alterations would maintain sympathetic hyperactivity and parasympathetic dysfunction, while it is well documented that these autonomic alterations predict morbidity and mortality in these populations (Malliani et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, our work reinforces some studies showing functional and structural alterations of the insula in cardiovascular diseases such as hypertension (Marins, Iddings, Fontes, & Filosa, ) or heart failure (Song, Roy, Fonarow, Woo, & Kumar, ). These insula alterations would maintain sympathetic hyperactivity and parasympathetic dysfunction, while it is well documented that these autonomic alterations predict morbidity and mortality in these populations (Malliani et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…In particular, a neurovascular remodeling of the insular cortex was revealed in hypertension, which may contribute to the maintenance of sympathetic hyperactivity and of hypertension (Marins et al, ). In heart failure, Song et al () reported functional and structural alterations in the insula correlated with autonomic dysfunctions. Lastly, insular strokes have been associated with increased mortality (Laredo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, decreased left Ic response to the Valsalva maneuver reported by Song et al, (2018) was suggested to be associated with decreased parasympathetic nervous system activity in HF patients. Oppenheimer, Gelb, Girvin, and Hachinski (1992) have defined a site involved in cardiovascular regulation in the Ic.…”
Section: Aberrant Left Insular Cortex Response: a Possible Pathogenesmentioning
confidence: 93%
“…
We have read the very interesting study by Song, Roy, Fonarow, Woo, and Kumar (2018) who showed that functional magnetic resonance imaging (MRI) responses of left insular cortex (Ic) in heart failure (HF) patients were delayed or decreased according to the magnitude of the Valsalva maneuver and that the impaired functional response of Ic had significant correlation with the degree of tissue changes.In earlier studies, the cardiovascular system has been suggested to be regulated by a central autonomic network (CAN) that consisted of the Ic, the anterior cingulate gyrus, and the amygdala (Nagai et al, 2017;Nagai, Hoshide, & Kario, 2010). In drug-refractory epilepsy patients, right hemispheric inactivation was associated with an increase in high frequency (HF) of the heart rate (HR) and blood pressure (BP), and the left hemispheric inactivation was associated with an increase in low frequency (LF) of HR and BP.
…”
mentioning
confidence: 99%
See 1 more Smart Citation